Gender Parameters of Acoustic Means of Communication Actualization in the Works of Volodymyr Lys (Linguostylistic Studies, 2018)
The article highlights the issue of linguistic means of nonverbalism representation in V. Lys's novels Jacob's Century and Solo for Solomiia with a focus on the acoustic components. The emphasis is laid on the extra-linguistic characteristics dominance in the artistic texts: laughter, crying, sobbing, coughing, whistling, spitting, etc. The most frequent are the language means for conveying such nonverbal codes as crying and laughing, which primarily mark women's communicative behavior. The main verbal actualizers are the key nouns laughter, weep, tear, and verbs to laugh/burst out laughing, chuckle, cry, weep, sob, etc. Typically male markers of non verbal means include cough, whistle, and spitting, for the actualization of which the author uses the supporting lexemes to cough, to whistle, to spit/spit out, cough, etc. Nominations of prosodic means have different degrees of explication in literary texts. To actualize the prosodic component, V. Lys uses the key verbs to say, to speak, supporting noun voice, and a wide range of attributive identifiers, such as cheerful, loud, icy, gentle, soft, obeisant, pleasant, serious, weak, sweet, compassionate, tired, hard, trembling, anxious, hoarse, twittering, etc.The percentage of nominations with an acoustic component in the descriptions of female behavior is rather high in the novel Solo for Solomia. It is due to the author's desire to make the image of the main character more vivid and expressive. The phrasemes based on crying (cry, tears, sob, crying, weep) represent the most numerous group in the descriptions of acoustic means of female behavior. To explicate a woman's crying, the writer uses attributive lexemes bitterly, passionately, quietly, loudly, sincerely, as well as phraseological constructions with a non-verbal component: wash with tears, give way to tears, burst into tears, rolling tears, choking on tears. Actualizing women's vocal/phonal behavior, V. Lys uses a large number of nominations of prosodic means, verbalizes pauses, or situational silence. The study has revealed that the expressiveness of language representatives is enhanced by figurative markers - metaphors, comparisons, epithets, metonymy, oxymorons, etc. Acoustic means allow to make an artistic image more expressive, to create a dynamic portrait of the hero, to describe his/her feelings. However, the domineering share in the acoustic characteristics of the characters' behavior is the voice (tone, timbre, pitch), primarily female.
Keywords: nonverbal communication; paraverbal means of communication; acoustic means; extralinguistics; prosody; verbalization